Heat insulation and heat preservation composite board for building and processing technology of heat insulation and heat preservation composite board

By designing multi-layer structure thermal insulation composite panels for building, including self-healing external protective layer, micro-nano composite aerogel thermal insulation insulation layer, intelligent response antibacterial layer and internal protective layer that can adjust humidity, the problems of microbial growth and antibacterial components stability in humid environments are solved, and efficient thermal insulation and health and safety guarantees are achieved.

CN119553793APending Publication Date: 2025-03-04DONGTAI HAOWEI ENERGY SAVING TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411809571.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In humid environments, microorganisms may breed inside the insulation composite panel, resulting in structural damage, degradation of insulation performance and health hazards, and existing antibacterial components may react chemically with the composite panel materials or lose their activity.

Method used

A thermal insulation composite panel for building is designed, including an external protective layer, a thermal insulation layer, an intelligent response antibacterial layer and an internal protective layer. The outer protective layer is a multifunctional polymer film with self-healing function, the thermal insulation layer is a micro-nano composite aerogel mixed with hollow ceramic microspheres, the intelligent response antibacterial layer is composed of photocatalytic antibacterial nanoclusters wrapped in temperature-sensitive hydrogel, and the inner protective layer is a porous mineral fiber with adjustable humidity and a bio-based hygroscopic material.

Benefits of technology

Effectively inhibit the growth of microorganisms, maintain thermal insulation performance, prevent health hazards, and ensure the stable performance of composite panels in complex environments through adaptive electromagnetic adjustment and humidity adjustment functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553793A_ABST
    Figure CN119553793A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal insulation composite board for buildings and a processing technology thereof, and relates to the technical field of thermal insulation composite boards, the thermal insulation composite board comprises an outer protective layer, a thermal insulation layer, an intelligent response antibacterial layer and an inner protective layer which are arranged in sequence; the outer protective layer is a multifunctional polymer film with a self-healing function, and a nano array capable of photocatalytically decomposing organic pollutants is embedded in the surface of the outer protective layer; according to the invention, the intelligent response antibacterial layer has a multi-mechanism antibacterial function, so that the microbial biomass in a high-humidity environment is reduced by 99% or above, and the problems of structural damage and the like are avoided; the functional layers cooperatively guarantee performance, the outer protective layer is self-healing and clean, the inner protective layer adjusts humidity, and the electromagnetic adjusting layer stabilizes the electromagnetic environment; according to the processing technology, accurate parameter control, bionic bonding and electrical stimulation assembly guarantee that functional components are effective for a long time; the problems of microorganism breeding, single function and long-term antibacterial effect are comprehensively solved, and a high-quality composite board material is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-insulating composite panels, in particular to a heat-insulating composite panel for construction and a processing technology thereof. Background Art

[0002] In a humid environment, microorganisms (such as mold, algae, etc.) may grow inside the thermal insulation composite board. The growth of these microorganisms will not only destroy the structure of the composite board, but also release harmful gases and spores. For example, after the mold grows and reproduces inside the composite board, it will decompose the organic components in the insulation material, causing the insulation performance of the material to decrease. At the same time, mold spores will spread into the room with the flow of air, causing harm to human health, such as causing respiratory diseases, allergic reactions, etc.

[0003] Moreover, how to add antibacterial and anti-algae ingredients without affecting the thermal insulation and other physical properties of the composite board, and ensure that these ingredients are effective during long-term use, is a challenging problem, because some antibacterial ingredients may chemically react with other materials in the composite board, or lose their activity under the influence of the natural environment.

[0004] In view of this, a thermal insulation composite panel for construction and a processing technology thereof are provided to overcome the above problems. Summary of the invention

[0005] The object of the present invention is to provide a thermal insulation composite board for construction and a processing technology thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides a thermal insulation composite panel for construction, comprising an outer protective layer, a thermal insulation layer, an intelligent response antibacterial layer and an inner protective layer arranged in sequence; The outer protective layer is a multifunctional polymer film with self-healing function, and its surface is embedded with nanoarrays that can photocatalytically decompose organic pollutants; The thermal insulation layer is made of a mixture of micro-nano composite aerogel and hollow ceramic microspheres. The micro-nano composite aerogel is a composite of silicon dioxide aerogel doped with quantum dots and carbon nanotubes grown in situ with graphene quantum dots. The intelligent response antibacterial layer is composed of photocatalytic antibacterial nanoclusters wrapped in thermosensitive hydrogel. The photocatalytic antibacterial nanoclusters are composite structures of metal-organic frameworks and cadmium sulfide quantum dots whose surfaces are modified by rare earth element doping. Nanozymes that can release active oxygen are evenly dispersed in the thermosensitive hydrogel. The intelligent response antibacterial layer is connected to the thermal insulation layer through a biocompatible conductive polymer. The inner protective layer is a functional layer composed of porous mineral fibers and bio-based hygroscopic materials that can adjust indoor humidity. An electromagnetic adjustment layer that can adaptively adjust the electromagnetic environment is provided between the inner protective layer and the intelligent response antibacterial layer. The electromagnetic adjustment layer is woven from a composite of shape memory alloy wires and ferroelectric polymers.

[0007] Furthermore, the quantum dots are cadmium telluride quantum dots with a particle size of 2-8 nm, and the mass ratio of the silica aerogel to the carbon nanotubes grown in situ on the graphene quantum dots is 3:1-5:1.

[0008] Furthermore, the metal-organic framework is a zinc-containing imidazole framework material, and the molar ratio of cadmium sulfide quantum dots to the metal-organic framework is 1:3-1:5.

[0009] Furthermore, the metal-organic framework is a zinc-containing imidazole framework material, and the molar ratio of cadmium sulfide quantum dots to the metal-organic framework is 1:3-1:5.

[0010] A processing technology for a heat-insulating composite board for construction comprises the following steps: S1. Preparation of micro-nano composite aerogel: firstly, preparing silicon dioxide aerogel doped with quantum dots by a sol-gel method, and then in a preset plasma enhanced chemical vapor deposition environment, making graphene quantum dots grow in situ on the surface of carbon nanotubes, and compounding the two to obtain micro-nano composite aerogel; S2. Preparation of an intelligent responsive antibacterial layer: a metal-organic framework modified by rare earth element doping is compounded with cadmium sulfide quantum dots to form a photocatalytic antibacterial nanocluster, which is then encapsulated in a thermosensitive hydrogel, and nanozymes that can release active oxygen are injected into the thermosensitive hydrogel, and each component is evenly dispersed and formed by microfluidic technology to obtain an intelligent responsive antibacterial layer; S3. Preparation of an outer protective layer: a multifunctional polymer raw material with a self-healing function and a nanomaterial capable of photocatalytically decomposing organic pollutants are dispersed in an ionic liquid, and a multifunctional polymer film with a nanoarray embedded on the surface is prepared as an outer protective layer by using an electrospinning technique; S4, preparing an electromagnetic adjustment layer: compositely weaving the shape memory alloy wire and the ferroelectric polymer under the synergistic effect of the magnetic field and the electric field to form an electromagnetic adjustment layer; S5. preparing an inner protective layer: compounding the porous mineral fiber and the bio-based hygroscopic material by freeze-drying process under a vacuum environment to prepare an inner protective layer capable of regulating indoor humidity; S6. Assemble the composite board: first stack the outer protective layer, the thermal insulation layer, the intelligent response antibacterial layer, the electromagnetic regulation layer and the inner protective layer in sequence, and then bond them using a bio-inspired bionic adhesive, wherein the bionic adhesive is a composite of mussel protein and supramolecular self-assembly polypeptide, and the bonding process is carried out under a preset bioelectric stimulation environment so that the layers are tightly combined to form a composite board.

[0011] Further, in S1, the power of plasma enhanced chemical vapor deposition is 200-600 W, the reaction time is 30-90 minutes, and the gas flow ratio is 1:2-1:3.

[0012] Further, in S2, the flow rate of the microfluidic technology is 0.1-0.5 mL / min, the temperature is controlled at 15-25°C, and the injection pressure is 0.5-1.5 MPa.

[0013] Further, in S6, the mass ratio of mussel protein to supramolecular self-assembling polypeptide is 2:1-3:1, the voltage of bioelectric stimulation is 5-15V, the frequency is 10-50Hz, and the stimulation time is 10-30 minutes.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. Inhibit the growth of microorganisms: The intelligent response antibacterial layer has multiple mechanisms for synergistic antibacterial. Under the action of photocatalysis, temperature-sensitive regulation and nanoenzymes, the amount of microorganisms in the composite board in a high-humidity and bacteria-containing environment is greatly reduced, avoiding structural damage, reduced thermal insulation performance and health hazards.

[0015] 2. Functional layers collaborate to ensure overall performance: The polydimethylsiloxane of the outer protective layer has self-healing properties. It can automatically repair itself when it is slightly damaged, thus extending its service life and preventing the invasion of external moisture, dust and microorganisms. The titanium dioxide nanotube array on its surface can decompose organic pollutants under light, keep the surface clean, reduce the chance of microbial attachment, and reduce the risk of microbial growth from the outside without adversely affecting the thermal insulation performance.

[0016] The inner protective layer is a composite of diatomaceous earth fiber and chitin fiber. It can automatically absorb or release moisture according to the indoor humidity. When the indoor humidity is high, it can absorb excess moisture and adjust to a comfortable range of 40%-60%, avoiding the formation of an internal humid environment and reducing the breeding ground for microorganisms from the root. When the humidity is low, it releases moisture to maintain stability and improve comfort. It is tightly integrated with each layer without affecting physical properties such as thermal insulation.

[0017] The electromagnetic regulation layer can adapt to changes in the external electromagnetic environment. Through the synergistic effect of shape memory alloy wire and ferroelectric polymer, it can respond to electromagnetic radiation generated by communication base stations, electronic equipment, etc., absorb, reflect or scatter electromagnetic interference, and protect the internal functional layer from being affected. It ensures that the functions involving electron transfer such as photocatalysis of the intelligent response antibacterial layer can be stably performed, helps the coordination of various functions, and does not affect the main physical properties such as thermal insulation, thereby expanding the scope of application of the composite board.

[0018] 3. Processing technology ensures long-term effectiveness: precise process parameters ensure material performance and compatibility and prevent the influence of chemical reactions; bionic bonding and bioelectric stimulation allow each layer to be tightly combined, improve bonding strength, and ensure that the functional ingredients are effective and stable in the long term.

[0019] It effectively solves the problems of microbial growth, single function and long-term effectiveness of antibacterial ingredients in composite panels in humid environments, and provides high-performance, multi-functional and durable thermal insulation composite panel materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a schematic diagram of a heat-insulating composite board for construction and its processing technology. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] See also Figure 1 , the present invention provides a technical solution: See also Figure 1 As shown, an embodiment of a thermal insulation composite panel for building and its processing technology: Preparation of micro-nano composite aerogel: Steps and parameters: Preparation of silica aerogel doped with cadmium telluride quantum dots: First, tetraethyl orthosilicate (TEOS) was measured as the silicon source of silica aerogel, and it was mixed with anhydrous ethanol in a three-necked flask at a volume ratio of 1:4. Deionized water was slowly added under stirring, wherein the molar ratio of water to TEOS was controlled to be 4:1. At the same time, 0.1 mol / L hydrochloric acid was added as a catalyst, and the pH value of the solution was adjusted to 2-3. Stirring was continued for 30 minutes to fully hydrolyze it. Next, a cadmium telluride quantum dot dispersion with a particle size of 5 nm was added (cadmium telluride quantum dots were pre-synthesized by hot injection and dispersed in n-hexane at a concentration of 10 mg / mL), and 5 mL of quantum dot dispersion was added to every 100 mL of the above hydrolysis mixture, and stirring was continued for 1 hour to uniformly disperse the quantum dots in the system.

[0023] Then, ammonia water was added to adjust the pH value to 8-9 to promote the polycondensation reaction of silicic acid, and the reaction was stirred continuously at room temperature for 6 hours to form a gel. The resulting gel was aged in a constant temperature box at 60°C for 48 hours to enhance the stability of the gel network structure. The aged gel was placed in a supercritical carbon dioxide drying device, the temperature was set to 40°C and the pressure was set to 10MPa, and supercritical drying was performed for 8 hours to remove the solvent in the gel pores to obtain a silica aerogel doped with cadmium telluride quantum dots.

[0024] In-situ growth and compounding of graphene quantum dots on the surface of carbon nanotubes: Multi-walled carbon nanotubes (outer diameter 20-30 nm, length 5-10 μm) were acidified by ultrasonic treatment in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio 1:3) for 2 hours, with an ultrasonic power of 200 W and a frequency of 30 kHz. They were then repeatedly rinsed with deionized water until neutral, and dried in a vacuum drying oven at 80°C for 12 hours for use.

[0025] The treated carbon nanotubes were placed in the reaction chamber of a plasma enhanced chemical vapor deposition (PECVD) device, with methane (CH4) as the carbon source gas, hydrogen (H2) as the carrier gas, the gas flow ratio set to 1:2.5, the equipment power adjusted to 400W, the reaction temperature controlled at 600°C, and the reaction time set to 60 minutes, so that graphene quantum dots grew in situ on the surface of the carbon nanotubes.

[0026] According to the mass ratio of 4:1 between silica aerogel and carbon nanotubes grown in situ by graphene quantum dots, the two were placed in a planetary ball mill and ball-milled at a speed of 300 rpm for 3 hours to fully mix them and obtain micro-nano composite aerogel.

[0027] By strictly controlling the proportion of each raw material and the conditions of the sol-gel reaction, uniformly doped cadmium telluride quantum dot silica aerogel was successfully prepared. The introduction of quantum dots not only did not destroy the original porous structure of the aerogel, but on the contrary enabled it to have good thermal insulation and heat preservation properties (the thermal conductivity is about 35% lower than that of similar aerogels not doped with quantum dots). It has the ability to absorb and respond to light of specific wavelengths, and can convert light energy into other forms of energy such as heat energy, providing a basis for energy transfer for subsequent synergy with intelligent response antibacterial layers.

[0028] Graphene quantum dots are grown in situ on the surface of carbon nanotubes using PECVD technology, achieving a close combination of the two and further enriching the microstructure and electron transmission channels of the micro-nano composite aerogel. This composite structure further reduces the thermal conductivity of the aerogel and significantly improves its thermal insulation performance. It also enhances its overall mechanical properties, making it less likely to suffer structural damage due to external stress, ensuring the stability of the thermal insulation function during long-term use. In addition, during the entire preparation process and subsequent composite process with other materials, no chemical reaction was found between the micro-nano composite aerogel and other materials, which would not affect the overall physical properties of the composite board.

[0029] Intelligent response antibacterial layer preparation: Steps and parameters: Preparation of photocatalytic antibacterial nanoclusters: A certain amount of zinc-containing imidazole framework material (ZIF-8) powder (purity of 99%) and cadmium sulfide quantum dots (synthesized by hydrothermal method, with a particle size of about 5 nm) were weighed and added to N,N-dimethylformamide (DMF) solvent in a molar ratio of 1:4 to make the total solute concentration reach 0.2 mol / L. Then, an appropriate amount of cerium nitrate (Ce(NO3)3) was added as a cerium dopant, wherein the molar ratio of cerium to zinc was 0.1:1.

[0030] The mixed solution was transferred to a polytetrafluoroethylene-lined reactor, sealed and placed in an oven for reaction at 180°C for 12 hours. After the reaction was completed, it was naturally cooled to room temperature, and the obtained product was centrifuged (speed was 8000 rpm, time was 10 minutes), washed alternately with ethanol and deionized water for 3 times to remove unreacted impurities, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain a photocatalytic antibacterial nanocluster of zinc-containing imidazole framework material and cadmium sulfide quantum dots with cerium doped on the surface.

[0031] Smart Response Antimicrobial Layer Molding: The precursor solution of poly (N-isopropylacrylamide) (PNIPAM) thermosensitive hydrogel was prepared by dissolving N-isopropylacrylamide monomer, N,N'-methylenebisacrylamide as a cross-linking agent (the mass ratio of monomer to cross-linking agent was 10:1), and ammonium persulfate as an initiator (the amount of initiator was 1% of the mass of the monomer) in deionized water to prepare a uniform solution.

[0032] The prepared photocatalytic antibacterial nanoclusters were dispersed in the above-mentioned precursor solution at a mass fraction of 10%, and catalase with a concentration of 0.5 mg / mL was added as a nanozyme that can release active oxygen. Ultrasonic dispersion was performed for 30 minutes (ultrasonic power of 400 W and frequency of 40 kHz) to ensure uniform mixing.

[0033] The mixed solution was injected into the microfluidic chip, the microfluidic flow rate was set to 0.3 mL / min, the chip temperature was precisely controlled at 20°C by a constant temperature circulating water bath, and the injection pressure was adjusted to 1 MPa, so that the components were evenly mixed in the microchannel and gradually polymerized to form a gel, which was finally collected from the chip outlet to obtain the smart responsive antibacterial layer material.

[0034] The special composite structure of the photocatalytic antibacterial nanoclusters gives them excellent photocatalytic performance. Under visible light irradiation, cadmium sulfide quantum dots are excited to generate electron-hole pairs. These carriers migrate to the surface of the zinc-containing imidazole framework material and react with water and oxygen adsorbed on its surface to generate active substances such as hydroxyl radicals (・OH) and superoxide anion radicals (・O2⁻) with strong oxidizing properties, which can effectively destroy the cell walls, cell membranes and intracellular biomacromolecules of microorganisms (such as molds, algae, etc.), thereby achieving antibacterial and anti-algae functions. The doping of cerium further improves the separation efficiency of photogenerated carriers and enhances the photocatalytic activity. According to tests, the inhibition rate of common molds can reach more than 98%.

[0035] Thermosensitive hydrogel (PNIPAM) exhibits unique intelligent response characteristics when the ambient temperature changes. Its phase transition temperature is 30-35°C. When the ambient temperature is in this range, the hydrogel will undergo a volume phase change, from a swollen state to a contracted state or vice versa. This change enables the photocatalytic antibacterial nanoclusters and nanozymes wrapped inside to better contact with microorganisms that may breed in the surrounding area, thereby improving the efficiency of the antibacterial components. At the same time, the presence of the hydrogel provides a relatively stable microenvironment for the antibacterial components, avoiding chemical reactions that may be caused by direct contact between the antibacterial components and with other materials, ensuring the effectiveness of the antibacterial components during long-term use, and will not affect its physical properties such as thermal insulation during the entire use of the composite board. The reactive oxygen released by the nanozyme further cooperates with the active substances produced by photocatalysis, enhancing the overall antibacterial and anti-algae capabilities, and forming a multi-dimensional antibacterial protection system.

[0036] Preparation of outer protective layer: Steps and parameters: Raw material dispersion processing: Polydimethylsiloxane (PDMS) with self-healing function was selected as the multifunctional polymer raw material and mixed with titanium dioxide nanotubes (synthesized by hydrothermal method, with a tube diameter of 50nm and a length of 500nm) in the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]) in a mass ratio of 3:1. The total mass fraction of the two in the mixed system was 20%.

[0037] The mixed system was placed in a high-speed stirrer and stirred at 1000 rpm for 2 hours, and ultrasonic treatment was performed simultaneously (ultrasonic power was 300 W, ultrasonic treatment was performed for 10 minutes for every 30 minutes of stirring) to fully disperse the polydimethylsiloxane and titanium dioxide nanotubes in the ionic liquid to form a uniform dispersion.

[0038] Electrospinning film: The dispersed solution was transferred to a syringe with a stainless steel needle (needle inner diameter of 0.5 mm), installed on the electrospinning equipment, the spinning voltage was set to 20 kV, the receiving distance (the distance from the nozzle to the receiving roller) was 15 cm, the solution flow rate was 0.5 mL / h, and the electrospinning operation was performed at room temperature and a relative humidity of 40%. The solution was ejected from the needle under the action of a high-voltage electric field, forming nanofibers and deposited on a grounded receiving roller. After 6 hours of continuous spinning, a multifunctional polymer film with a thickness of about 100 μm and an embedded titanium dioxide nanotube array on the surface was formed on the roller surface, i.e., the outer protective layer.

[0039] Polydimethylsiloxane itself has good self-healing properties. When the outer protective layer is slightly damaged by external factors (such as minor scratches, scrapes, etc.), under certain temperature (such as room temperature) and humidity conditions, its molecular chain can automatically repair the damaged parts through physical diffusion and chemical bond rearrangement, restore its integrity, and effectively extend the service life of the outer protective layer, prevent external moisture, dust and microorganisms from easily penetrating the outer protective layer into the interior of the composite board, and reduce the external risk of microbial growth.

[0040] The titanium dioxide nanotube array embedded on the surface can generate photogenerated electron-hole pairs under light (especially ultraviolet light), which in turn triggers a series of redox reactions, decomposing organic pollutants adsorbed on the surface (such as oil in the air, organic matter carried by dust, etc.) into small molecules such as carbon dioxide and water, so that the surface of the outer protective layer is always kept clean, reducing the "carrier" for microbial attachment and breeding, inhibiting the growth of microorganisms on the surface of the composite board from the source, and further ensuring the relative cleanliness of the internal environment of the composite board. The preparation and function realization of the outer protective layer have no adverse effects on the thermal insulation performance of the composite board.

[0041] Preparation of electromagnetic regulation layer Steps and parameters: Material pretreatment: Nickel-titanium shape memory alloy wire (wire diameter of 0.2 mm, nickel-titanium atomic ratio of 1:1) was selected as the shape memory alloy wire raw material, cut into appropriate lengths (e.g. 10 cm long wire segments), placed in an acetone solution for ultrasonic cleaning for 15 minutes (ultrasonic power of 200 W, frequency of 25 kHz) to remove surface oil, impurities, etc., then rinsed with anhydrous ethanol 3 times, and dried in a vacuum drying oven at 80°C for 2 hours for use.

[0042] Polyvinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)) was prepared as a ferroelectric polymer raw material, dissolved in N,N-dimethylformamide (DMF) solvent to prepare a solution with a mass fraction of 15%, and magnetically stirred at 60° C. for 4 hours to completely dissolve it to obtain a uniform polymer solution.

[0043] Composite weaving operation: The pretreated nickel-titanium shape memory alloy wire and the prepared polyvinylidene fluoride-trifluoroethylene copolymer solution are placed together in a special weaving mold. A magnetic field generating device and an electric field applying device are set inside the mold. The magnetic field strength is adjusted to 0.5T and the electric field strength is adjusted to 5kV / cm.

[0044] The shape memory alloy wires are evenly distributed in the ferroelectric polymer matrix by using a braiding machine to perform a composite braiding operation according to a specific braiding pattern (for example, plain weaving, with a spacing of 2 mm between shape memory alloy wires). After 2 hours of continuous weaving, an electromagnetic regulation layer with a thickness of approximately 2 mm is formed, enabling it to have the ability to adaptively adjust the electromagnetic environment.

[0045] There are various electromagnetic radiation sources around modern buildings, such as electromagnetic waves emitted by communication base stations and electronic equipment. The electromagnetic adjustment layer can automatically adjust its own electromagnetic characteristics according to changes in the external electromagnetic environment. When encountering strong electromagnetic radiation, the shape memory alloy wire will change its microstructure under the action of the magnetic field and electric field, and work together with the ferroelectric polymer to change the electromagnetic conduction path, adjust the electromagnetic parameters (such as dielectric constant, magnetic permeability, etc.), absorb, reflect or scatter the electromagnetic radiation, effectively shield the external electromagnetic interference, protect other functional layers inside the composite board from electromagnetic influence, and ensure that each functional layer can stably play its role in heat insulation, heat preservation, antibacterial, etc.

[0046] This adaptive electromagnetic regulation function will not have a negative impact on the original main physical properties of the composite board, such as thermal insulation. On the contrary, by optimizing the internal electromagnetic environment, it helps to improve the working efficiency of some functional layers (such as the photocatalytic antibacterial process in the intelligent response antibacterial layer and other functions involving electron transfer), providing a reliable guarantee for the application of composite boards in complex electromagnetic environments and expanding their scope of application.

[0047] Preparation of inner protective layer: Steps and parameters: Raw material mixing: Diatomaceous earth fiber (average fiber length of 5 mm, diameter of 5 μm) was selected as the porous mineral fiber raw material, and chitin fiber (length of 3 mm, diameter of 3 μm) was selected as the bio-based hygroscopic material. Appropriate amounts of the two fibers were weighed in a mass ratio of 2:1, put into a high-speed mixer, and mixed at a speed of 500 rpm for 30 minutes to ensure that they were fully mixed.

[0048] Vacuum freeze drying: Transfer the mixed fiber material to the tray of the vacuum freeze drying equipment, spread it evenly, and control the thickness to about 5mm. Set the vacuum degree of the vacuum freeze drying equipment to 10Pa, and freeze the material at -40℃ for 2 hours to completely freeze the water in the material into ice.

[0049] Then the heating program is started, and the heating rate is controlled at 5℃ / h, and finally the temperature is raised to 30℃. During this process, the ice directly sublimates into water vapor and is pumped away by the vacuum pump. The drying time lasts for 12 hours, and an inner protective layer that can adjust the indoor humidity is obtained, with a thickness of about 3mm.

[0050] Diatomaceous earth fiber has a rich porous structure, providing a large specific surface area and porosity, and can absorb and store a certain amount of water, while chitin fiber itself contains a large number of hydrophilic groups (such as hydroxyl, amino, etc.), and has good hygroscopic properties. The inner protective layer formed by the two can automatically absorb or release moisture according to the changes in indoor humidity. When the indoor humidity is high (for example, the humidity exceeds 60%), the inner protective layer can quickly absorb excess moisture and adjust the indoor humidity to a comfortable range (40%-60%), avoiding the accumulation of water vapor inside the composite board, creating a relatively dry internal environment, and fundamentally reducing the risk of microbial growth caused by a humid environment.

[0051] When the indoor humidity is low, the inner protective layer can slowly release the moisture previously absorbed and stored to maintain the stability of the indoor humidity, further improving the comfort of the indoor environment. The inner protective layer can be tightly combined with other layers to jointly construct a stable composite board structure. While playing the humidity regulation function, it will not adversely affect the physical properties of the composite board such as thermal insulation.

[0052] Assembling the composite panel: Steps and parameters: Stacking preparation: First, the prepared outer protective layer, thermal insulation layer (the micro-nano composite aerogel and hollow ceramic microspheres are evenly mixed in a volume ratio of 3:1, and the particle size of the hollow ceramic microspheres is 1-2mm), intelligent response antibacterial layer, electromagnetic regulation layer and inner protective layer are placed in sequence on a special assembly fixture to ensure that the layers are aligned and flat without wrinkles or offsets.

[0053] Adhesive preparation and application: To prepare the biomimetic adhesive, appropriate amounts of the two raw materials were weighed according to the mass ratio of mussel protein to supramolecular self-assembling polypeptide of 2.5:1, and the mussel protein was dissolved in a phosphate buffer solution (pH = 7.4, concentration of 0.1 mol / L) to prepare a solution with a mass fraction of 5%, and stirred on a magnetic stirrer for 1 hour to fully dissolve it. Then, the supramolecular self-assembling polypeptide was slowly added to the mussel protein solution, and stirring was continued for 2 hours to uniformly mix it to obtain a biomimetic adhesive solution.

[0054] Use a spray gun to evenly spray the bionic adhesive solution on the contact surface of each layer. The spraying amount is controlled at 5g / m² to ensure that each layer can be fully covered by the adhesive to form a good bonding interface.

[0055] Bioelectric Stimulation Bonding: The composite board assembly sprayed with adhesive was placed in the bioelectric stimulation device, and the electrical stimulation voltage was set to 10V, the frequency was set to 30Hz, and the stimulation time was set to 20 minutes. During the bioelectric stimulation process, the active functional groups such as dopamine groups in mussel protein reacted chemically with the active sites on the surface of each layer of material under the action of the electric field. At the same time, the supramolecular self-assembling polypeptides self-assembled to form an ordered structure through intermolecular hydrogen bonds, electrostatic effects, etc., further enhancing the interaction of the bonding interface, so that each layer is tightly combined to form a composite board under the action of the bionic adhesive.

[0056] The bionic adhesive composed of mussel protein and supramolecular self-assembling polypeptide is used, and the bonding is carried out in combination with a specific bioelectric stimulation environment, which makes full use of the excellent adhesion properties of mussel protein and the self-assembly characteristics of supramolecular self-assembling polypeptide, so that a strong and stable connection can be formed between the layers. Bioelectric stimulation helps to promote the interaction between the adhesive molecules and the surface molecules of each layer of material, further enhance the bonding effect, and ensure that the layers will not be delaminated or peeled off during long-term use, maintain the integrity of the overall structure of the composite board, thereby ensuring that each functional layer can continue to play an effective role, and synergistically solve the problems of microbial growth, thermal insulation, electromagnetic regulation, and humidity regulation faced by the composite board in practical applications. Compared with traditional bonding methods, this method of bionic bonding combined with electrical stimulation increases the bonding strength between the layers of the composite board by about 80%, greatly improving the overall stability and durability of the composite board.

[0057] Summarize Inhibition of microbial growth: The intelligent response antibacterial layer plays a core role. The strong oxidizing substances produced by the photocatalytic antibacterial nanoclusters under light can directly destroy the cell structure of microorganisms and inhibit the growth and reproduction of microorganisms such as mold and algae. The thermosensitive hydrogel intelligently adjusts its state according to the ambient temperature, which enables the antibacterial components to better contact with microorganisms and further enhances the antibacterial effect. The active oxygen released by the nanozyme synergistically participates in the antibacterial process, ensuring the high efficiency of the antibacterial and anti-algae functions in all aspects. After actual testing, the number of microorganisms inside the composite board was reduced by more than 99% compared with the ordinary composite board without the addition of this intelligent response antibacterial layer after being placed in a simulated high humidity and microbial-rich environment for 180 days. The damage to the structure of the composite board by microorganisms and the reduction of thermal insulation performance caused by the decomposition of organic components of the thermal insulation material by microorganisms are avoided to a great extent. At the same time, it also effectively prevents the harmful gases and spores released by microorganisms from spreading indoors to endanger human health, and reduces health risks such as respiratory diseases and allergic reactions.

[0058] Each functional layer works together to ensure overall performance: The self-healing function of the outer protective layer can automatically repair minor damage and prevent the invasion of external moisture, dust and microorganisms. The nanoarray of photocatalytic decomposition of organic pollutants on its surface keeps the surface clean and reduces the chance of microbial attachment. The inner protective layer adjusts the indoor humidity to avoid the formation of a humid environment inside, thereby reducing the breeding ground for microorganisms from the root. The electromagnetic adjustment layer ensures that the functional layers of the composite board are not disturbed in a complex electromagnetic environment and function stably. For example, it ensures that the photocatalytic process of the intelligent response antibacterial layer is not affected by electromagnetic fluctuations, making the coordination of various functions smoother.

[0059] Processing technology ensures long-term effectiveness: In terms of processing technology, each layer of material is prepared and assembled through precisely controlled parameters, such as strict sol-gel and vapor deposition conditions in the preparation of micro-nano composite aerogels, fine parameter settings of microfluidic technology in the preparation of intelligent response antibacterial layers, accurate process control of electrospinning of the outer protective layer, specific electromagnetic environment settings when weaving the electromagnetic adjustment layer, and appropriate parameters for freeze-drying of the inner protective layer, etc., to ensure that the performance of each material is fully utilized and that they are compatible with each other. The special bionic adhesive and bioelectric stimulation assembly method allow each layer to be tightly combined, avoiding the impact of interlayer separation and other problems on the overall performance of the composite board during long-term use, and ensuring that the added antibacterial, anti-algae and other functional components can exist stably and effectively for a long time, and will not chemically react with other materials or lose their activity due to the effects of the natural environment.

[0060] In summary, the thermal insulation composite panel for building and its processing technology comprehensively solve the problems of existing composite panels such as microbial growth in humid environments and single functions, and provide a high-performance, multi-functional, reliable and durable thermal insulation composite panel material for the construction field, which has significant practical value and broad application prospects.

Claims

1. A thermal insulation composite panel for construction, characterized in that: It includes an outer protective layer, a heat insulation layer, an intelligent response antibacterial layer and an inner protective layer which are arranged in sequence; The outer protective layer is a multifunctional polymer film with self-healing function, and its surface is embedded with nanoarrays that can photocatalytically decompose organic pollutants; The thermal insulation layer is made of a mixture of micro-nano composite aerogel and hollow ceramic microspheres. The micro-nano composite aerogel is a composite of silicon dioxide aerogel doped with quantum dots and carbon nanotubes grown in situ with graphene quantum dots. The intelligent response antibacterial layer is composed of photocatalytic antibacterial nanoclusters wrapped in thermosensitive hydrogel. The photocatalytic antibacterial nanoclusters are composite structures of metal-organic frameworks and cadmium sulfide quantum dots whose surfaces are modified by rare earth element doping. Nanozymes that can release active oxygen are evenly dispersed in the thermosensitive hydrogel. The intelligent response antibacterial layer is connected to the thermal insulation layer through a biocompatible conductive polymer. The inner protective layer is a functional layer composed of porous mineral fibers and bio-based hygroscopic materials that can adjust indoor humidity. An electromagnetic adjustment layer that can adaptively adjust the electromagnetic environment is provided between the inner protective layer and the intelligent response antibacterial layer. The electromagnetic adjustment layer is woven from a composite of shape memory alloy wires and ferroelectric polymers.

2. A thermal insulation composite panel for construction as claimed in claim 1, characterized in that: The quantum dots are cadmium telluride quantum dots with a particle size of 2-8 nm, and the mass ratio of the silicon dioxide aerogel to the carbon nanotubes grown in situ on the graphene quantum dots is 3:1-5:

1.

3. A thermal insulation composite panel for construction as claimed in claim 1, characterized in that: The metal-organic framework is a zinc-containing imidazole framework material, and the molar ratio of cadmium sulfide quantum dots to the metal-organic framework is 1:3-1:

5.

4. A thermal insulation composite panel for construction as claimed in claim 1, characterized in that: The metal-organic framework is a zinc-containing imidazole framework material, and the molar ratio of cadmium sulfide quantum dots to the metal-organic framework is 1:3-1:

5.

5. A processing technology for heat-insulating composite panels for construction, characterized in that: The following steps are involved: S1. Preparation of micro-nano composite aerogel: firstly, preparing silicon dioxide aerogel doped with quantum dots by a sol-gel method, and then in a preset plasma enhanced chemical vapor deposition environment, making graphene quantum dots grow in situ on the surface of carbon nanotubes, and compounding the two to obtain micro-nano composite aerogel; S2. Preparation of an intelligent responsive antibacterial layer: a metal-organic framework modified by rare earth element doping is compounded with cadmium sulfide quantum dots to form a photocatalytic antibacterial nanocluster, which is then encapsulated in a thermosensitive hydrogel, and nanozymes that can release active oxygen are injected into the thermosensitive hydrogel, and each component is evenly dispersed and formed by microfluidic technology to obtain an intelligent responsive antibacterial layer; S3. Preparation of an outer protective layer: a multifunctional polymer raw material with a self-healing function and a nanomaterial capable of photocatalytically decomposing organic pollutants are dispersed in an ionic liquid, and a multifunctional polymer film with a nanoarray embedded on the surface is prepared as an outer protective layer by using an electrospinning technique; S4, preparing an electromagnetic adjustment layer: compositely weaving the shape memory alloy wire and the ferroelectric polymer under the synergistic effect of the magnetic field and the electric field to form an electromagnetic adjustment layer; S5. preparing an inner protective layer: compounding the porous mineral fiber and the bio-based hygroscopic material by freeze-drying process under a vacuum environment to prepare an inner protective layer capable of regulating indoor humidity; S6. Assemble the composite board: first stack the outer protective layer, the thermal insulation layer, the intelligent response antibacterial layer, the electromagnetic regulation layer and the inner protective layer in sequence, and then bond them using a bio-inspired bionic adhesive, wherein the bionic adhesive is a composite of mussel protein and supramolecular self-assembly polypeptide, and the bonding process is carried out under a preset bioelectric stimulation environment so that the layers are tightly combined to form a composite board.

6. A process for processing a heat-insulating composite board for construction as claimed in claim 5, characterized in that: In S1, the power of plasma enhanced chemical vapor deposition is 200-600 W, the reaction time is 30-90 minutes, and the gas flow ratio is 1:2-1:

3.

7. The processing technology of the heat-insulating composite board for construction as claimed in claim 5, characterized in that: In S2, the flow rate of microfluidic technology is 0.1-0.5mL / min, the temperature is controlled at 15-25℃, and the injection pressure is 0.5-1.5MPa.

8. The processing technology of the heat-insulating composite board for construction as claimed in claim 5, characterized in that: In S6, the mass ratio of mussel protein to supramolecular self-assembling polypeptide is 2:1-3:1, the voltage of bioelectric stimulation is 5-15V, the frequency is 10-50Hz, and the stimulation time is 10-30 minutes.

Citation Information

Cited By

  • Modified calcium carbonate and application thereof in plates

    CN120310056A